Internet Financial Report And Determinants of The Quality of Financial Statements of Non-Profit Organizations - Hardiyanto, Nico; Ahmar, Nurmala; Etty Merawati, Endang (Green Publisher Indonesia, 2023)
The purpose of this research was to assess the elements that influence the quality of non-profit financial statements and the moderation of voluntary disclosures on the Internet Financial Report.